2021
DOI: 10.1186/s13048-021-00864-3
|View full text |Cite
|
Sign up to set email alerts
|

CXCL2-mediated ATR/CHK1 signaling pathway and platinum resistance in epithelial ovarian cancer

Abstract: Tumor microenvironment and chemokines play a significant role in cancer chemoresistance. This study was designed to reveal the important role of CXCL2 in platinum resistance in epithelial ovarian cancer (EOC). Differently expressed (DE) genes were screen out based on analysis of GSE114206 dataset in GEO database. The expression of DE chemokines was further validated in platinum- resistant and sensitive EOC. Cell viability assay and cell apoptosis assay were performed to explore the roles of CXCL2 in EOC. Cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…As a class of chemokines, CXCL2 is involved in the repair process of in ammatory injury and is involved in cell migration, adhesion and immune response. A large number of studies have shown that CXCL2 plays a role in promoting the occurrence and development of cancer in colorectal cancer, ovarian cancer, prostate cancer and chronic lymphocytic leukemia [29] . CXCL2 is involved in cell proliferation, apoptosis, tumor formation and development, and is closely related to the generation and differentiation of megakaryocytes [30] .…”
Section: Discussionmentioning
confidence: 99%
“…As a class of chemokines, CXCL2 is involved in the repair process of in ammatory injury and is involved in cell migration, adhesion and immune response. A large number of studies have shown that CXCL2 plays a role in promoting the occurrence and development of cancer in colorectal cancer, ovarian cancer, prostate cancer and chronic lymphocytic leukemia [29] . CXCL2 is involved in cell proliferation, apoptosis, tumor formation and development, and is closely related to the generation and differentiation of megakaryocytes [30] .…”
Section: Discussionmentioning
confidence: 99%
“…CCL21 can be regulated by ACKR4 to suppress antitumor immunity [ 37 ]. Additionally, Nei et al [ 38 ] found that CXCL2 overexpression can maintain the stemness of cells in epithelial ovarian cancer while activating ATR/CHK1 signaling pathway and promoting cell resistance to cisplatin. Group-2 innate lymphoid cells promote HCC progression through CXCL2-neutrophil-induced immunosuppression [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal immune-related gene expression is strongly associated with immune infiltrating cells in various ways, making it a potential diagnostic and therapeutic target that provides new avenues for studying tumor molecular mechanisms of tumors [30][31][32]. Additionally, tumor-related genes influence various biological processes involved in tumor formation and treatment though activating distinct signaling pathways [33][34][35]. In this study, ADGRD1 was significantly linearly correlated with 149 immune-related genes in NSCLC, and for GO functional annotation analysis, these genes were most enriched in terms "positive regulation of leukocyte activation", "positive regulation of cell activation" , and "leukocyte migration" in BP category, "external side of plasma membrane", "secretory granule lumen", and "cytoplasmic vesicle lumen" in CC category, and "receptor ligand activity", "cytokine activity", and "cytokine receptor binding" in MF category.…”
Section: Discussionmentioning
confidence: 99%